THE EXISTENCE OF TESTAMENTARY LAW IN THE ISLAMIC DIVISION OF INHERITANCE - Fatmawati, Ida Nuriya; Asis, Asis; Nadid, Erdin (Media Keadilan: Jurnal Ilmu Hukum, 2023)
This study wants to highlight the position of wills in Islamic inheritance law, where as is well known there is a basic principle that the property of a deceased person should be divided in accordance with the provisions of the Quran and Sunnah. Then the problem is the position of the will of the deceased in Islamic law. Where this is still a basic question because so far wills are often ignored in the division of inheritance. The method used in this study is an interdisciplinary approach, namely socio-legal where this approach not only looks normatively but also the impact caused by rules or laws. This study wants to answer; (1) What is the position of the will in Islamic law?, (2) To what extent do religious courts recognize the will of a deceased person?. The conclusion of this study is that the legality of wills has not been fully recognized in Islamic inheritance law, this is evidenced by the existence of inheritance decisions that tend to prioritize the division of inheritance in Islamic inheritance law.